Reviews of new publications - Holmes, Derek A (KUKILA, 1996)
Collar, N.J., M.J. Crosby & A.J. Stattersfield. 1994. Birds to Watch 2: The World List of Threatened Birds. BirdLife Conservation Series No. 4, BirdLife International, Cambridge Dekker R.W.R.J. & P.J.K. McGowan (Compilers). 1995. Megapodes: an action plan for their conservation 1995-1999. IUCN and the World Pheasant Association McGowan P.J.K. & P.J Garson (Compilers). 1995. Status survey and action plan 1995-1999: Pheasants. Compiled on behalf of the World Pheasant Association/BirdLife/SSC Pheasant Specialist Group Sözer, R. & V. Nijman. 1995. Behavioural ecology, distribution and conservation of the Javan Hawk-eagle Spizaetus barteisi Stresemann, 1924. Verslagen en Technische Gegevens No. 62. Institute of Systematics and Population Biology, University of Amsterdam